Wisdom Begins in Wonder - BOULKROUN, Meriem; ASSESS, Mohamed Tahar (University of Eloued جامعة الوادي, 2016)
In many language classrooms, students are assessed solely on the basis of their linguistic productions.However, this is not enough since schools are, and have always been, places where students are supposed to learn to think. The challenge isto teach students higher order thinking skills and to train them to think critically.Most educators would agree that their students are not as proficient at these kinds of thinking since textbooks and other teaching materials often consist of tasks that require low-level skills and ignore higher order thinking skills. Over the years, educators such as Bloom (1956) and Gardner (1983) have worked on the development of a simple, practical framework to help teachers be more effective and systematic in teaching their students how to think by proposing various ways to describe the components of thinking. Those frameworks changed the way teachers taught and assessed students. Nowadays, educators shifted concern from performance-oriented goals to learning-oriented goals. To develop the skills and strategies necessary for deep and careful thinking, students must be engaged in tasks that require critical thinking and problem solving. Socratic questioning provides a good method to enhance learners‘ critical thinking.
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued